Energy Recovery Strategies in CO2 Compression Using an Integrated Supercritical Rankine Cycle - Panagiotis Kazepidis; Panos Seferlis; Athanasios I. Papadopoulos (Chemical Engineering Transactions)
One of the leading technologies for reducing industrial CO2 emissions is Carbon Capture and Storage (CCS). Existing publications address the high energy requirements of the capture process while overlooking the subsequent compression process required for CO2 transportation, which also exhibits intense energy needs. This work aims to investigate and compare the energy requirements of two alternative methods to the conventional process for pressurising captured CO2 to 150 bar. After the capture process, CO2 is typically at near atmospheric pressure, requiring multi-stage compression due to compressor limitations. After each compression stage, cooling is required to maintain the fluid close to the optimal temperature for further compression. The proposed alternative methods utilise the compressed CO2, which is in a supercritical state (sCO2), as the working fluid to recover heat that is available among the compression stages. One of the alternative methods uses sCO2 in an integrated open supercritical Rankine cycle (sRC) at each cooling stage. The other method, apart from the sRC, heats the CO2-rich liquid stream before the regeneration column of the capture process at the final compression stage. The compression processes are designed for a CO2 stream of 2,779 t/d, representing the typical captured CO2 mass flow from a 400 MW power plant. Results suggest that the case of combining sRC and the CO2-rich stream heating is the most energy-efficient among the tested cases, requiring 5.11 MW less than the sRC-only case and 4.31 MW less than the conventional compression case without intercooling.